已知m(m-3)-(m²-3n)=9,则(m²+n²)/2-mn=?
2个回答
因为m(m-3)-(m^2-3n)=9
所以-3m+3n=9
n-m=3
所以 m^2+n^2-2nm=9
所以 (m^2+n^2)/2=(9+2nm)/2
所以 原式=4.5+mn-mn=4.5
相关问题
已知m-n=2 则3m^2-6mn+3n^2-9=
已知m+n=5,mn=3,则m2n+mn2=______.
已知m+n=2 mn=-4,则2(mn-3m)-3(2n-mn)
已知mn/m+n=2求3m-5mn+3n/-m+3mn-n
已知mn/m+n=2,求3m-5mn+3n/(-m)+3mn-n
已知m+n=3,mn=-2,则(m-2)(n-2)=______.
已知m-n=3,mn=-3,求(-m-4n-mn)-(2mn-2m-3n)-(3mn+2n-2m)的值
已知9m^2-6mn+n^2=0,则分式m+3n/2n-3m的值是
已知m(m-3)-(m^2-3n)=9,求(m^2+n^2)/2-mn的值.
已知m-n=4,mn=-1,求:(2mn+2m+3n)+(3mn+2n-2m)-(m+4n+mn)